SELF-EFFICACY GURU MATEMATIKA DALAM MENGHADAPI DINAMIKA PEMBELAJARAN DI MASA PANDEMI COVID 19 - Sarah Inayah; Dadang Juandi; Rizki Dwi Siswanto; Shelly Morin (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2022)
The purpose of this research is to reveal and describe how the self-efficacy of mathematics teachers in Cianjur towards the dynamics of learning during the Covid-19 pandemic. The research was conducted in Cianjur Regency. The methodology used is descriptive quantitative method. The technique of collecting data is through questionnaires given by purposive and snowball sampling techniques. Data analysis uses descriptive statistics which do not aim to make conclusions about the entire population but rather help understand the details of the sample. The results showed that the overall self-efficacy of Mathematics Teachers in Cianjur was in the moderate category. Likewise, four of the seven constructs on teacher self-efficacy are Mathematics Knowledge Self-efficacy (KS), Instructional Self-efficacy (IS), Outcome Expectancy (OE) and Technology Literacy (TL) in the medium category. This means that teachers believe they have the ability to carry out their duties in the midst of a pandemic even though they still need development related to the four constructs. However, the other constructs namely Motivational Self-efficacy (MS), Engagement Self-efficacy (ES), and Disciplinary (as in classroom management) Self-efficacy (DS) are in the high category. This condition shows that teachers are able to provide motivation, students can be actively involved in learning and learning continues to be carried out conducive even though learning is carried out in the midst of a pandemic condition.